2017
DOI: 10.1017/rdc.2017.100
|View full text |Cite
|
Sign up to set email alerts
|

Changes in CO2 Emission Sources in Mexico City Metropolitan Area Deduced from Radiocarbon Concentrations in Tree Rings

Abstract: We present radiocarbon (14C) in tree rings from Mexico City and a reconstruction of fossil CO2 concentrations for the last five decades, as part of a research program to understand the 14C dynamics in this complex urban area. Background values were established by 14C concentrations in tree rings from a nearby clean area. Agreement between background and NH-zone 2 values indicate Taxodium mucronatum is a good biomonitor for annual atmospheric 14C variations. Values for the urban tree rings were significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…The equations we obtained here (eq. 10 and 12) are different than reported by other authors in the tree-ring radiocarbon literature (Rakowski et al 2008a, Beramendi-Orosco et al 2017.…”
Section: Calculation Of the Co2 Concentration Of Fossil Fuels Origin ...contrasting
confidence: 65%
See 1 more Smart Citation
“…The equations we obtained here (eq. 10 and 12) are different than reported by other authors in the tree-ring radiocarbon literature (Rakowski et al 2008a, Beramendi-Orosco et al 2017.…”
Section: Calculation Of the Co2 Concentration Of Fossil Fuels Origin ...contrasting
confidence: 65%
“…We believe the equation reported by others (Rakowski et al 2008a, Beramendi-Orosco et al 2017, based on the mass balance equations of Levin et al (1989Levin et al ( , 2003, is probably wrong. We recommend using our equations (10 and 12) depending on the required variables.…”
Section: Discussionmentioning
confidence: 75%
“…Tree δ 13 C ratios in our study were slightly lower than those reported for P. hartwegii in nearby forests (Gómez‐Guerrero et al, 2013; Silva et al, 2015). However, these values consistently reflect a dilution effect ( 13 C‐Suess effect) of CO 2 due to the release of 13 C‐depleted CO 2 from combusted fossil C fuels into the atmosphere (Figure 4a) (Beramendi‐Orosco et al, 2018). After correcting for the Suess effect, our results indicate that even with short‐time periods of tree ring measurements, such as 17 years, it is possible to capture high‐frequency events related to year‐to‐year variations in tree physiological performance, which scale up to landscapes.…”
Section: Discussionmentioning
confidence: 92%
“…The Mexico City Metropolitan Area (MCMA) is a complex megacity with a mixture of CO 2 emission sources, where atmospheric radiocarbon ( 14 C) variability is influenced mainly by changes in fossil fuel combustion and biomass burning from residential combustion, agricultural burning and wildfires in the mountains surrounding the valley, common during the dry season (winter and spring) (Beramendi-Orosco et al 2015, 2018. Previous studies have reported Δ 14 C levels in MCMA up to 75‰ and 27‰ higher than regional background values during the hot and dry season (Vay et al 2009 andBeramendi-Orosco et al 2015, respectively), attributed to the release of 14 C-enriched CO 2 resulting from the burning of soil organic matter during agricultural and wild fires in the basin, suggesting this is a significant CO 2 emission source as it cancels out the 14 C dilution resulting from the vast amount of fossil fuels burned this metropolitan area with high population density.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported Δ 14 C levels in MCMA up to 75‰ and 27‰ higher than regional background values during the hot and dry season (Vay et al 2009 andBeramendi-Orosco et al 2015, respectively), attributed to the release of 14 C-enriched CO 2 resulting from the burning of soil organic matter during agricultural and wild fires in the basin, suggesting this is a significant CO 2 emission source as it cancels out the 14 C dilution resulting from the vast amount of fossil fuels burned this metropolitan area with high population density. These observations could result in an underestimation of the atmospheric fossil CO 2 concentration in the MCMA, hampering the direct use of 14 C as a tracer of fossil CO 2 emissions in such a complex urban area (Beramendi-Orosco et al 2018). main fuels.…”
Section: Introductionmentioning
confidence: 99%